Analisis Reaksi Pasar Terhadap Perubahan Peraturan Kemenperin Nomor 31/M-IND/PER/8/2017 Pada Perusahaan Manufaktur di BEI - Napitupulu, Erving Anggiatma; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
This study aims to determine the market reaction to changes in regulations in the Ministry of Industry. The research methodology used is event study to examine the information content of an announcement. The subject of this research is a manufacturing company listed on the Indonesia Stock Exchange, the sample selection is done by purposive sampling, which is a population that meets certain criteria with the aim of getting a representative sample in accordance with the specified criteria. The data analysis technique used was the one sample t test on hypothesis 1 and the Mann Whitney test for hypothesis 2. The test results of the market reaction to all samples showed a reaction to changes in the Ministry of Industry regulation No. 31 / M-IND / PER / 8/2017 on the company manufacturing on the third day before the announcement of regulatory changes and the second day after the announcement of regulatory changes. There are differences in the reaction between manufacturing companies and non-manufacturing companies to changes in regulations of the Ministry of Industry No. 31 / M-IND / PER / 8/2017 in the third day period before the announcement of regulatory changes and the second day after the announcement of regulatory changes. Keywords: market reaction, abnormal return, information content